Iceland's Financial Crisis - Jackson, James K. (2008)
On November 19, 2008, Iceland and the International Monetary Fund (IMF) finalized an agreement on a $6 billion economic stabilization program supported by a $2.1 billion loan from the IMF. Following the IMF decision, Denmark, Finland, Norway, and Sweden agreed to provide an additional $2.5 billion. Iceland's banking system had collapsed as a culmination of a series of decisions the banks made that left them highly exposed to disruptions in financial markets. The collapse of the banks also raises questions for U.S. leaders and others about supervising banks that operate across national borders, especially as it becomes increasingly difficult to distinguish the limits of domestic financial markets. Such supervision is important for banks that are headquartered in small economies, but operate across national borders. If such banks become so overexposed in foreign markets that a financial disruption threatens the solvency of the banks, the collapse of the banks can overwhelm domestic credit markets and outstrip the ability of the central bank to serve as the lender of last resort. This report will be updated as warranted by events. CRS Report for Congress.